The concept “Child” in English phraseology: semantic, cognitive, linguacultural perspectives - Orazgalieva , Ayjamal Marat qizi (The Lingua Spectrum, 2026)
This study examines the phraseological representation of the concept “child” in the English linguistic worldview, focusing on how child-related lexemes function within idiomatic expressions. Phraseological units are regarded as carriers of cultural memory, reflecting social values, stereotypes, and historical experience. The material of the study consists of phraseological units extracted from authoritative lexicographic sources, including Kunin’s Phraseological Dictionary and major English idiom dictionaries. The analysis reveals that the concept “child” is verbalised through multiple semantic models, such as social typification, metaphorical reinterpretation, evaluative characterisation, and euphemistic usage. Special attention is paid to metaphor-based phraseological units, where child-related imagery serves as a cognitive standard for simplicity, emotionality, naivety, and dependence. The study also demonstrates that such units frequently extend beyond literal reference to denote professional roles, social identities, and behavioural patterns. Additionally, the research highlights culturally specific values, including discipline, responsibility, and independence, reflected in phraseological usage.